Role of interleukin‐17 in the pathogenesis of perianal abscess and anal fistula: a clinical study on 50 patients with perianal abscess. Issue 3 (25th October 2018) - Wang, Jian‐Ping; Cai, Cheng; Du, Jin‐Lin; Shi, Hong‐Qi; Liu, Qing‐Wei; Dai, Zhi‐Hui; Zhong, Zhi‐Feng
Abstract : Background: To investigate the role of interleukin (IL)‐17 in tissue and peripheral blood of perianal abscess and anal fistula. Methods: Patients with primary perianal abscess ( n = 50) admitted to Jinhua Municipal Central Hospital between March 2003 and August 2004 were enrolled. Fifty patients with mixed haemorrhoids, who showed no perianal abscess or anal fistula, were also recruited as the control. After surgery, patients were followed up for 6 months. Protein and gene expression of IL‐17 was determined in surgically harvested anal tissues and peripheral blood, respectively. The relationship between IL‐17 and clinical pathological features were analysed. Results: As shown by immunohistochemistry of anorectal tissues, the positive rate of IL‐17 protein was higher in the perianal abscess group than in the control group. In patients with perianal abscess, the expression of IL‐17 significantly correlated with the diameter of the abscess ( P = 0.013), the wound surface healing time ( P = 0.010) and the progression into anal fistula ( P = 0.003). For the gene expression of IL‐17 in peripheral blood cells, the level was significantly higher in patients with perianal abscess comparing to the control group (0.4350 ± 0.1190 versus 0.1785 ± 0.1230, P ≤ 0.001). Comparing to the recovery group, patients with their perianal abscess progressed to anal fistula showed higher levels of IL‐17 gene expression ( P = 0.014). Conclusions: Expression of IL‐17 was increased in the anorectal tissues and peripheral blood of patients with perianal abscess and anal fistula. IL‐17 may play an important role in the pathogenesis of perianal abscess and anal fistula.